Role of long non-coding RNA in inflammatory bowel disease - Hu, Yufei; Lu, Yifan; Fang, Yi; Zhang, Qizhe; Zheng, Zhuoqun; Zheng, Xiaojuan; Ye, Xiaohua; Chen, Yanping; Ding, Jin; Yang, Jianfeng (Frontiers in Immunology, 2024)
Inflammatory bowel disease (IBD) is a group of recurrent chronic inflammatory diseases, including Crohn's disease (CD) and ulcerative colitis (UC). Although IBD has been extensively studied for decades, its cause and pathogenesis remain unclear.Existing research suggests that IBD may be the result of an interaction between genetic factors, environmental factors and the gut microbiome. IBD is closely related to non-coding RNAs (ncRNAs). NcRNAs are composed of microRNA(miRNA), long non-coding RNA(lnc RNA) and circular RNA(circ RNA). Compared with miRNA, the role of lnc RNA in IBD has been little studied. Lnc RNA is an RNA molecule that regulates gene expression and regulates a variety of molecular pathways involved in the pathbiology of IBD. Targeting IBD-associated lnc RNAs may promote personalized treatment of IBD and have therapeutic value for IBD patients. Therefore, this review summarized the effects of lnc RNA on the intestinal epithelial barrier, inflammatory response and immune homeostasis in IBD, and summarized the potential of lnc RNA as a biomarker of IBD and as a predictor of therapeutic response to IBD in the future.